Performance evaluation of computer and communication systems milestones and future challenges ; IFIP WG 6.3/7.3 International Workshop, PERFORM 2010 in Honor of Günter Haring on the Occasion of his emeritus celebration Vienna, Austria, October 14-16, 2010, revised selected papers - Haring, Günter 1943-; Hummel, Karin Anna; Hlavacs, Helmut; Gansterer, Wilfried (Lecture Notes in Computer Science, 2011)
This Festschrift volume is published in honor of Günter Haring on the occasion of his emerital celebration and contains invited papers by key researchers in the field of performance evaluation presented at the workshop Performance Evaluation of Computer and Communication Systems - Milestones and Future Challenges, PERFORM 2010, held in Vienna, Austria, in October 2010. Günter Haring has dedicated most of his scientific professional life to performance evaluation and the design of distributed systems, contributing in particular to the field of workload characterization. In addition to his own contributions and leadership in international research projects, he is and has been an excellent mentor of young researchers demonstrated by their own brilliant scientific careers. The 20 thoroughly refereed papers range from visionary to in-depth research papers and are organized in the following topical sections: milestones and evolutions; trends: green ICT and virtual machines; modeling; mobility and mobile networks; communication and computer networks; and load balancing, analysis, and management.